A Combined Experimental and Theoretical Study on the Corrosion Inhibition and Adsorption Behaviour of Quinoxaline Derivative During Carbon Steel Corrosion in Hydrochloric Acid - Zarrok,H. (2012)
The corrosion inhibitive effects of 2-(4-methylphenyl)-1,4-dihydroquinoxaline (Q1) on carbon steel surface in hydrochloric acid solution was studied using weight loss measurements, electrochemical impedance spectroscopy (EIS), Tafel polarization techniques and quantum chemical approach, using the density functional theory (DFT). Inhibition efficiency increased with increase in concentration of the inhibitor. The degree of surface coverage of the adsorbed inhibitor was determined by weight loss technique, and it was found that the results obeyed Langmuir adsorption isotherm. Tafel polarization data indicated that this inhibitor is of mixed type. EIS shows that charge- transfer resistance increases and the capacitance of double layer decreases with the inhibitor concentration, confirming the adsorption process mechanism. Trends in the calculated molecular properties (e.g., dipole moment, HOMO and LUMO energies) were compared with trends in the experimentally determined inhibition efficiency. The results show that trends in the quantum chemical descriptors are in agreement with the experimentally determined inhibition efficiencies.